Peran Guru Dalam Pengembangan Literasi Digital - Dian Nastiti; Indah Ayu Permana P (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This Community Service Program examines efforts to enhance teachers' digital literacy in online learning. In the era of information technology, information and digital literacy have become crucial. The execution of this Community Service Program aims to improve teachers' understanding of digital literacy. This activity is conducted online in the second weeks of June and July. The provided topics include